A rare cause of primary adrenal insufficiency - Zaharudin, Mohd Radzli; Thambiah, Subashini C.; Samsudin, Intan Nureslyna; Abdul Hamid, Hanisah (Universiti Putra Malaysia, 2021)
Adrenal hypoplasia congenita (AHC) is a rare inherited condition due to the failure of the adult zone of the adrenal cortex to develop despite normal development of its foetal counterpart. Affected patients are usually asymptomatic at birth but will present with clinical features of acute adrenal insufficiency during early infancy. It is clinically indistinguishable from the more common congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency. Here, we report a case of a one-month-old male infant with primary adrenal insufficiency (PAI) whose initial laboratory investigations revealed hyponatraemia and severe hyperkalaemia. The early onset of PAI with the absence of ambiguous genitalia and low baseline and adrenocorticotropic-stimulated 17-hydroxyprogesterone and undetectable dehydroepiandrosterone sulfate levels, suggest the possibility of AHC in this infant. Genetic analysis is crucial to confirm the diagnosis of this condition and to differentiate from CAH as their prognoses and management differ.